The end of personal rule in Indonesia Golkar and the transformation of the Suharto Regime - Masuhara, Ayako 1969- (Kyoto area studies on Asia, 2015)
Motivated by on-the-ground experiences during Indonesia's period of political turmoil in the early 2000s following the collapse of the Suharto regime, this book systematically explains the structure of the Suharto regime while revealing its political dynamism. The primary goal is to account for the transformations that Suharto's personal rule underwent during 30 years in power and explain its end. The book focuses on the 'personal rule system' that Suharto employed, analyzing its transition and collapse in a groundbreaking thesis that draws on archival materials from major political institutions, as well as interviews with some of the key political protagonists. The concept 'co-opting type personal rule' is proposed to address the following questions: What concept can best capture the Suharto regime and the diverse array of personal rule systems and better explain the characteristics of each type? How can we analyze personal rule regimes that end in relatively peaceful transitions rather than revolution or violent coup? Thesis. (Series: Kyoto Area Studies on Asia - Vol. 24) [Subject: Asian Studies, Indonesian Studies, Politics]